Pengaruh Beban Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Badan Penelitian Dan Pengembangan Provinsi Sumatera Utara - Tri Kartika Yudha; Abdul Rohim Musprianto; Nilawati Nasti; Muhammad Prasetyo Wibowo (Jurnal Prodi Fakultas Ekonomi-UISU, 2023)
Human resources are essentially one of the assets that play an important role in achieving company goals. Human resources are company assets that must be maintained. Empowerment of human resources that is managed regularly and systematically will produce qualified and competitive quality human resources. In this rapidly growing era, companies must be extra selective in selecting competitive, qualified and highly competitive human resources. The formulation in this study is how the influence of workload on employee performance in Balitbang, North Sumatra Province. The purpose of this study was to determine and analyze workload on employee performance in the Balitbang Province of North Sumatra. This research is quantitative descriptive. Data collection was carried out through interviews, questionnaires and documentation studies. The sample in this study was 52 people using Arikunto's theory. The questionnaires received back from respondents were 52 questionnaires. Variables are measured by testing the hypothesis using multiple linear regression analysis through the F test and t test. Based on the research results, it is known that workload has a negative and significant effect on employee performance at the Balitbang Province of North Sumatra. This is evident from the results of the t test where 0.000 0.05, Job satisfaction has a positive and significant effect on employee performance in the Balitbang Province of North Sumatra. This is evident from the results of the t test where 0.000 0.05. Workload (X1) and Job Satisfaction (X2) simultaneously have a positive and significant influence on employee performance, because f count f table, namely (14,972 3.19. Based on the results of data processing, the value of the coefficient of determination R2 is 0.379. This means that 37.9% of the variable dependent (Employee Performance) is influenced or explained by the independent variables namely workload and job satisfaction and the remaining 62.1% (100% -37.9%) is influenced or explained by other variables outside the variables used in this study